2015
DOI: 10.1038/pr.2015.149
|View full text |Cite
|
Sign up to set email alerts
|

Gestational and postnatal modulation of esophageal sphincter reflexes in human premature neonates

Abstract: BackgroundEffects of gestational age (GA) and postnatal maturation on upper and lower esophageal sphincter (UES and LES) reflex development remains unclear. We hypothesized very-preterm (VPT) born neonates (< 32 weeks GA) have delayed maturation of UES contractile reflex (UESCR) and LES relaxation reflex (LESRR) vs. preterm (PT) born (32–37 weeks GA) neonates.MethodsUsing provocative manometry, effects of 1263 graded mid-esophageal stimuli (air, liquid) on sensory-motor characteristics of UESCR and LESRR were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Studies in humans have reported similar reflexes in response to slow esophageal distension in full-term and preterm infants (8,11,12,15,17) in addition to esophagoglottal closure in response to rapid esophageal distension in adults and full-term (50) and preterm infants (13,14).…”
Section: Literature Data On Reflexes Originating From the Esophagusmentioning
confidence: 88%
“…Studies in humans have reported similar reflexes in response to slow esophageal distension in full-term and preterm infants (8,11,12,15,17) in addition to esophagoglottal closure in response to rapid esophageal distension in adults and full-term (50) and preterm infants (13,14).…”
Section: Literature Data On Reflexes Originating From the Esophagusmentioning
confidence: 88%
“…In the past, maturational changes of the LES function have been explored during dry swallows and in response to mid-esophageal provocations [11, 14, 28]. Pena et al [14] demonstrated shorter response latency to LES relaxation in response to liquid stimulation and longer LES relaxation in relation to age.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, all subjects were former preterm infants. While pharyngo‐esophageal motility does mature with increasing age, former preterm infants studied at term equivalent PMA have esophageal motility skills approaching those of infants born at term gestation . Therefore, the results are directly applicable to former preterm born infants when they reach term PMA, however, it is also appropriate to extrapolate the results as applicable as well to infants born at term gestation .…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Therefore, the results are directly applicable to former preterm born infants when they reach term PMA, however, it is also appropriate to extrapolate the results as applicable as well to infants born at term gestation. 50,51 As has been demonstrated for manometry analysis algorithms using Chicago Classification in adults, when dealing with a pediatric or neonatal population, modifications are necessary to account for changing parameters with patient age and size [19][20][21] ; however, the precise application of these adjustments is unknown for neonates. Our finding that the majority of the swallows analyzed fell into the 'weak' category for contractile vigor, despite the majority characterization of completeness of peristaltic wave, may indicate that modification indeed may be necessary in neonates for such categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation